Synergistic action of cyclic adenosine monophosphate- and calcium-mediated chloride secretion in a colonic epithelial cell line. - Cartwright, C A (1985)
Vasoactive intestinal polypeptide (VIP) and the calcium ionophore A23187 caused dose-dependent changes in the potential difference and the short circuit current (Isc) across confluent T84 cell monolayers mounted in modified Ussing chambers. Both VIP and A23187 stimulated net chloride secretion without altering sodium transport. Net chloride secretion accounted for the increase in Isc. When A23187 was tested in combination with VIP, net chloride secretion was significantly greater than predicted from the calculated sum of their individual responses indicating a synergistic effect. VIP increased cellular cyclic AMP (cAMP) production in a dose-dependent manner, whereas A23187 had no effect on cellular cAMP. We then determined whether VIP and A23187 activated different transport pathways. Earlier studies suggest that VIP activates a basolaterally localized, barium-sensitive potassium channel as well as an apically localized chloride conductance pathway. In this study, stimulation of basolateral membrane potassium efflux by A23187 was documented by preloading the monolayers with 86Rb+. Stimulation of potassium efflux by A23187 was additive to the VIP-stimulated potassium efflux. By itself, 0.3 microM A23187 did not alter transepithelial chloride permeability, and its stimulation of basolateral membrane potassium efflux caused only a relatively small amount of chloride secretion. However, in the presence of an increased transepithelial chloride permeability induced by VIP, the effectiveness of A23187 on chloride secretion was greatly augmented. Our studies suggest that cAMP and calcium each activate basolateral potassium channels, but cAMP also activates an apically localized chloride channel. Synergism results from cooperative interaction of potassium channels and the chloride channel.